Pengaruh Kontrol Diri terhadap Perilaku Phubbing dikalangan Mahasiswa - Tiwi, Lorensia Persiana; Upa, Muhamad Dae Pua; Apriliana, I Putu Agus (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Incredible technological advances have facilitated human activities such as communicating between individuals that take place indirectly. On the other hand, there is a phenomenon where individuals ignore the people around them because they are more focused on their mobile phones and do not look at their interlocutors. This condition is known as phubbing behaviour which includes communication disturbance and phone obsession. The current study examines the influence of self-control on phubbing behavior among university students. A quantitative approach with a comparative causal method was used by involving 50 students of the counseling guidance study program at Nusa Cendana University through a proportional stratified random sampling technique. The results showed that self-control in dominant students was in the low category with a percentage of 64%, while the level of phubbing behavior in dominant students was in the high category with a percentage of 76%. The results of hypothesis testing show that there is a significant influence between self-control on phubbing behavior among students. Furthermore, simple linear regression analysis obtained a coefficient of determination (R Square) of 0.483 which indicates that there is an influence of self-control on phubbing behavior at 48.3% and the remaining 51.7% is thought to be influenced by other factors not examined in this study. The negative form of influence between self-control and phubbing behavior indicates that the lower the self-control of students, the higher the phubbing behavior. Recommendations for the findings of this study are discussed.